Inhibition of Insulin‐Regulated Aminopeptidase (IRAP) by Arylsulfonamides. Issue 6 (21st November 2014) - Borhade, Sanjay R.; Rosenström, Ulrika; Sävmarker, Jonas; Lundbäck, Thomas; Jenmalm-Jensen, Annika; Sigmundsson, Kristmundur; Axelsson, Hanna; Svensson, Fredrik; Konda, Vivek; Sköld, Christian; Larhed, Mats; Hallberg, Mathias
Abstract The inhibition of insulin‐regulated aminopeptidase (IRAP, EC 3.4.11.3) by angiotenesin IV is known to improve memory and learning in rats. Screening 10 500 low‐molecular‐weight compounds in an enzyme inhibition assay with IRAP from Chinese Hamster Ovary (CHO) cells provided an arylsulfonamide (N‐(3‐(1H‐tetrazol‐5‐yl)phenyl)‐4‐bromo‐5‐chlorothiophene‐2‐sulfonamide), comprising a tetrazole in the meta position of the aromatic ring, as a hit. Analogues of this hit were synthesized, and their inhibitory capacities were determined. A small structure–activity relationship study revealed that the sulfonamide function and the tetrazole ring are crucial for IRAP inhibition. The inhibitors exhibited a moderate inhibitory potency with an IC50=1.1±0.5 μm for the best inhibitor in the series. Further optimization of this new class of IRAP inhibitors is required to make them attractive as research tools and as potential cognitive enhancers.